2017
DOI: 10.18510/ijmier.2017.323
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Preference of Private Hospitals to Public Hospitals in Oman

Abstract: Purpose:The objectives of the study are to analyze the factors which influence patients to go to private hospitals against public hospitals of Oman and to analyze the expectations of patients from the integrated public hospitals in Oman.Design/methodology/approach: The study was carried out with a well-defined questionnaire through which 251 survey samples were collected on a random sampling basis. Findings:The results of the study reveal that there is an association between the selection of hospital and servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…Other studies conducted in developing countries showed that private health facilities are preferred to public facilities due to several reasons, including more approachable and more helpful staff, easier access, well-equipped clinics with modern equipment and devices, and more professional healthcare providers who treat patients with respect and in a friendly manner. The only negative issue found to be associated with private clinics was the high cost of services as compared to the free cost of public facilities [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies conducted in developing countries showed that private health facilities are preferred to public facilities due to several reasons, including more approachable and more helpful staff, easier access, well-equipped clinics with modern equipment and devices, and more professional healthcare providers who treat patients with respect and in a friendly manner. The only negative issue found to be associated with private clinics was the high cost of services as compared to the free cost of public facilities [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo, aqueles que podiam tomar providências na fase inicial do acidente vascular cerebral em busca de atendimento frequentaram, geralmente, hospitais, especialmente privados. Razões para não buscar atendimento em hospital público foram previamente declaradas (10) e aqueles procuraram atendimento em hospital público de ensino o fizeram, em grande parte, porque confiavam na reputação deste tipo de serviço quanto à assistência de alta complexidade.…”
Section: Discussionunclassified
“…Hospitals in the public sector are considered less open to the development and upgradation of basic facilities [10]. Environmental hazards, front desk reception, OPD ticketing, and payments methods and ignorance of paramedical staff are the factors usually reported in different studies and collectively responsible for the decline in patient satisfaction level [11,12]. The results of our study demonstrated that in public sector hospitals 55.53% of patients were satisfied with the basic facilities provided by hospitals whereas in the private sector 73.2% of patients were satisfied.…”
Section: Discussionmentioning
confidence: 99%